Pemasaran budidaya ikan nila Desa Sungai Duren melalui analisis SOAR dalam perspektif ekonomi Islam - Arfah, Arfah; Dahlia, Dahlia; Heriyani, Heriyani; Fitriana, Fitriana (AL-Muqayyad, 2024)
This research aims to examine parot fish marketing strategies through SOAR (strength, opportunity, aspirations, result) analysis in an Islamic economic review in Sungai Duren sub-district, Jambi Province. The importance of this research is that parot fish is part of the freshwater fish cultivation commodity with urgent economic value. Marketing of parot fish between fish farmers, collectors or consumers can provide efficiency in activities in the field. However, this condition sometimes experiences market access problems, which have an impact on the continued existence of parot fish cultivation businesses. This research uses qualitative methods. The results of the research show that in order for parot fish cultivation to be successful in the future, it is necessary to change the parot fish cultivation strategy itself and change the marketing strategy, which was initially carried out in ponds, changing to the form of cages which are very popular with the public, so that the profits obtained are as expected.